PENGARUH PENERAPAN STRATEGI PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DISERTAI LKS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 SUNGAI BEREMAS KABUPATEN PASAMAN BARAT - Yulfianti, Melia; Rahmi, Rahmi; Haryono, Yulia (STKIP PGRI Sumbar, 2013)
Studying process which is taken place at SMPN 2 Sungai Beremas is tending to one way process, teacher is a centrall of all learning process. Teachers dominate all activities at class, and still many students cheat when doing exercise. This is why hasnât understanding mathematic concept well, proved by so many students got low mart. So this research is aim to know studentâs understanding of mathematical concept by using cooperative learning types Student Teams Achievem Division (STAD) with student work sheets is better than cooventional ways. The kind of research is experimental research. the population in this research is the eight class student of SMPN 2 Sungai Beremas academic year of 2013/2014. The sample is taken randomly, the experiment class is VIIIB and the control class is VIIIA. The instruments in this research is mathematical concept understanding test like essay. The result of research shows that students understanding of mathematical concept using cooperative learning types Student Teams Achievem Division (STAD) with student work sheets is better than conventional ways. Hypotesis test is using minitab with t-test, obtained P-value = 0,024 Â = 0,05 whichis specified, then it can be concluded that studentâs understanding of mathematical concept using cooperative learning Student Teams Achievem Division (STAD) with student work sheets is better than conventional ways that is used in control class.